ANALYSIS OF WLAN NETWORK HANDOVER PERFORMANCE USING RSSI AND THRESHOLD ON MOBILE DEVICES - Mhd Ikhsan Rifki; Muhammad Ikhsan; Rini Halila Nasution; Dysa Handira (INFOKUM, 2022)
Random user mobility on a WLAN network allows users to move away from the access point (AP) that serves them so it has an impact on the possibility of users losing connectivity to the communication network. This study aims to simulate handover performance at the Faculty of Science and Technology UIN North Sumatra to maintain network QoS by using the comparison method of RSSI AP1 and AP2 values ​​and comparing RSSI values ​​with Threshold values. The computational results on the RSSI comparison method with the threshold are carried out at a distance of 15 meters, and the comparison of the RSSI AP1 values ​​has dropped below the RSSI AP2 values ​​with values ​​of -64.35 dBm and -62.75 dBm respectively. Meanwhile, in the threshold method, the RSSI AP1 value is below the threshold so that the user connectivity service will be transferred to AP2. This research is expected so that the Faculty of Science and Technology can obtain information on the quality of WLAN network services through mobile devices.